Injury Severity of Ambulatory Patients Following Motor Vehicle Crash. Issue 1 (January 2021) - Stimson, Christopher
Abstract : Background: On-scene ambulatory status following a motor vehicle crash (MVC) serves as an informal marker of physiologic stability. The influence of ambulatory status after an MVC on trauma team activation and injury severity is infrequently studied, yet may alter the clinician's index of suspicion for injury. The purpose of this study is to describe the injury burden of ambulatory on-scene patients following an MVC. Methods: This is a prospective descriptive study of MVC patients arriving by emergency medical services (EMS), with trauma team activation, to a Midwestern Level I trauma center from July through December 2018. The EMS records were reviewed for wording that indicated the patient's ambulatory status following an MVC. Those denoted as "ambulatory on-scene" were included in this study. Of this subset, Injury Severity Score (ISS), hospital admission status, safety mechanisms utilized, crash scene description, and demographics were collected. Results: A total of 648 MVC patients with trauma activations were reviewed, of which 308 met criteria for study inclusion. The average ISS was 2.8, with a range of 0 to 30. The cohort was 51.3% male, with a hospital admission rate of 25.9%. Of the 308 trauma activations, six were total, and 302 were partial. Conclusion: This study of MVC patients with documented on-scene ambulation found that, although the average ISS was low, injuries and hospital admission were present in up to one-quarter of patients. Ambulatory status following an MVC while informative should not be used as a triage mechanism.